2017
DOI: 10.1099/jmm.0.000475
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of quinolone action and resistance: where do we stand?

Abstract: Quinolone antibiotics represent one of the most important classes of anti-infective agents and, although still clinically valuable, their use has been compromised by the increasing emergence of resistant strains, which has become a prevalent clinical problem. Quinolones act by inhibiting the activity of DNA gyrase and topoisomerase IV - two essential bacterial enzymes that modulate the chromosomal supercoiling required for critical nucleic acid processes. The acquisition of quinolone resistance is recognized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
238
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(254 citation statements)
references
References 58 publications
8
238
2
6
Order By: Relevance
“…Many studies have addressed drug resistance mechanisms, which can be classified into two classes [33]: one is the genetic and epigenetic alternations of tumor cells that affect drug sensitivity; the other is impairment of the drug delivery system of tumor cells. In this study, we found that downregulation of P-gp by AA effectively increased the drug sensitivity of A549/DDP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have addressed drug resistance mechanisms, which can be classified into two classes [33]: one is the genetic and epigenetic alternations of tumor cells that affect drug sensitivity; the other is impairment of the drug delivery system of tumor cells. In this study, we found that downregulation of P-gp by AA effectively increased the drug sensitivity of A549/DDP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Then, their association to plasmids has allowed their spread in other bacterial species. It is noted that PMQR determinants generally confer only low-level quinolone resistance that alone does not exceed the clinical breakpoint but they can favor the selection of additional resistance mechanisms [70].…”
Section: Discussionmentioning
confidence: 99%
“…This mode of resistance has been collectively termed "target protection" and generally involves the direct release of a cellular target from the inhibitory action of the antibiotic (41,42). Target protection has been reported for the ribosome and DNA replication (43)(44)(45), but to our knowledge, no example has been described to date for the protection of cell wall synthesis. We now propose that BceAB-type transporters act by target protection of the lipid II cycle.…”
Section: Attempted Depletion Of Upp Affects Transport Activity On a Gmentioning
confidence: 99%